Critical analysis of the usage of patient demographic and clinical records during doctor-patient consultations: a Malaysian perspective - Abd Ghani, Mohd Khanapi; Bali, Rajeev K.; Naguib, Rouf N.G.; Marshall, Ian M.; Wickramasinghe, Nilmini S. (Inderscience Enterprises Ltd, 2010)
The Lifetime Health Record (LHR) is the central key delivery component of Malaysia’s integrated telehealth application. The LHR consists of the summarised health records of every individual compiled from their Electronic Medical Record (EMR). The most important consideration however is that the patient health record should not only be available and accessible seamlessly, but also has the ability to be continuously captured by healthcare professionals. This research aims to analyse and identify the most crucial patient demographic and clinical records that are referred to and recorded by the doctors during the consultation encounter.